A Weird Way to Sustain a Near Fatal Neck Injury, A Case Report - Jha, Amit; Limbu, Tilak; Baral, Sovit Jung; Lamichhane, Donjon Bahadur; Regmi, Bibek (Med Phoenix, 2021)
Accidental injuries are common during festivals. With time, the traditional practices have been ill-defined and have turned out social misconduct and malpractice. Children and young adults barricade the road to extort money from the passerby in the name of tradition during festivals. Barricading roads occasionally results in loss of control over vehicles and falling down on the road sustaining trauma including neck injuries among the drivers. This is a report of a case of a young male biker who got trapped along the rope tied across the road and nearly strangulated to death.